Handbook of Fractional-Horsepower Drives - Stoelting, Hans-Dieter; Kallenbach, Eberhard; Amrhein, Wolfgang (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Fractional-Horsepower drives are crucial for all kinds of products, from simple domestic utensils to most complex technological applications. This handbook gives a practical overview on the available drives. It gives a comprehensive reference about design, functionality, properties, and applications of fractional horsepower drives and introduces into their control and the mechanical transducers. Additionally, the book shows us avenues for projecting new drives. With first English edition of the bestselling German book, the author address practicing engineers as well as students of electrical and mechanical engineering, control and mechatronics.